Business innovation statistics and the evolution of the Oslo Manual - Perani, Giulio (NOvation — Critical Studies of Innovation, 2019)
After the publication of the fourth (2018) edition of the Oslo Manual, a key methodological reference for producing innovation statistics at international level, a review of the definitions of innovation – or, better, business innovation – used by the community of official statisticians has to be recommended. The main reason for such a review is the need to assess to what extent the current Oslo Manual has benefited from the rich economic and management literature on firms’ innovation produced since the publication of the previous edition in 2005. It should also be pointed out that the current Manual was expected to fix some long-standing issues like that of properly accommodating service innovation in a statistical framework constantly biased towards innovation in tangible goods and technology-related phenomena. This article argues that these challenges have been only partially met. By reviving some concepts used in the past, such as the object-oriented approach to measure innovation, and being especially concerned to make the statistical framework designed to measure business innovation applicable in other sectors of the economy (including individuals and households), some specific features of the business innovation processes may have been neglected. The Manual discusses a wide array of issues regarding the economics of innovation and management practices, however it does not define a new consistent framework able to accommodate the demand for indicators about the influence on business innovation of the ongoing processes of digitalization, servitization or open innovation and, at least partially, to adopt a service-dominant logic.